STRATEGI PENGEMBANGAN DAYA TARIK WISATA TIRTA BERBASIS PARTISIPASI MASYARAKAT LOKAL DI DESA WISATA AAN, KABUPATEN KLUNGKUNG, BALI (Jurnal Destinasi Pariwisata, 2025)
This study analyzes the strategy for developing water-based tourism attractions based on local community participation in Aan Tourism Village, Klungkung Regency, Bali. Aan Village possesses significant water-based tourism potential, including attractions like Petapan Park, Aan Secret Waterfall, and Pelukatan Pesiraman, supported by amenities, accessibility, and diverse tourist activities. Local community participation predominantly aligns with the Spontaneous Participation type, characterized by the initiative and active involvement of POKDARWIS, BUMDes, Karang Taruna, and PKK in tourism management. However, challenges related to human resources and funding persist. Based on SWOT analysis, Aan Tourism Village's strategic position is in Quadrant I (Strengths-Opportunities), recommending an aggressive strategy. Proposed strategies include community-based digital promotion, strengthening community capacity through ecotourism training, initiating participatory conservation programs, and integrating local UMKM into the tourism value chain. The implementation of these strategies is expected to optimize the village's potential and foster sustainable and inclusive tourism development for the local community
Keywords: Water Tourism; Community Participation; Development Strategy; Community Based Tourism; Aan Tourism Village